Pengaruh Kualitas Pelayanan dan Electronic Word of Mouth Terhadap Keputusan Pembelian di Hotel Ra Suite Simatupang - Ratu Bilqis, Linda Desafitri; Taviprawati, Ervina; Ciu, Putri Yasmin (Jurnal Ilmiah Pariwisata, 2024)
The hotel industry in Indonesia, especially in Jakarta, is facing increasingly stringent challenges due to the increasing flow of tourists. Hotel RA Suite Simatupang needs to maintain and increase its market share by focusing on service quality and Electronic Word of Mouth (E-WOM). This research aims to analyze the influence of service quality and E-WOM on purchasing decisions. The research method uses a quantitative approach with multiple regression analysis, involving 100 respondents who have stayed at the hotel during 2023. Data was collected through a questionnaire with a Likert scale. The results of the analysis show that service quality and E-WOM have a significant effect on purchasing decisions, with 73.1% of the variation in decisions being explained by these two variables. Good service quality increases customer satisfaction and loyalty, while positive E-WOM shapes the perceptions and beliefs of potential guests. This research concludes that RA Suite Hotel management needs to improve service quality and utilize E-WOM to attract more customers. Suggestions are given for hotels to continue to innovate in services and actively manage online reviews to strengthen their reputation and attractiveness in the market. Keywords: service quality, electronic word of mouth, purchasing decisions